Sodium Valproate Combined With Topiramate vs. Sodium Valproate Alone for Refractory Epilepsy: A Systematic Review and Meta-Analysis - Ji, Zhen-Ye; Huang, Yi-Qian; He, Wen-Zhen (Frontiers in Neurology, 2022)
Background: Among antiepileptic drugs (AEDs), sodium valproate alone or in the combination of topiramate (TPM) for treating refractory epilepsy was controversial. This meta-analysis aimed to systematically evaluate the clinical effects of these two regimens in this population. Methods: Relevant studies up to August 2021 were identified through systematic searches of CNKI, Wanfang, PubMed, and Embase databases. We assessed the effectiveness and the frequency of absence seizures, atonic seizures, and tonic–clonic seizures. The included literature's risk of bias was evaluated using the Cochrane Collaboration's Risk of Bias tool. Sensitivity analysis was conducted to confirm the results' stability. STATA 15.0 was utilized for all pooled analyses in the included studies. Results: Totally 10 articles were determined for our meta-analysis, involving 976 patients with epilepsy in total (combined group, n = 488; monotherapy group, n = 488). The results of this meta-analysis indicated that the total effective rate of sodium valproate combined with TPM was higher than that of sodium valproate alone (random-effect model: OR = 3.52; 95% CI 1.47 to 8.47; p < 0.001; I2 = 73.8%). The frequency of absence seizures in the combined group was lower (fixed-effect model: WMD = −6.02; 95% CI −6.50 to −5.54; I2 = 0.0%) than that in the monotherapy group, with a statistical difference (p < 0.05). The combined group had lower frequency of atonic seizures (WMD = −4.56, 95% CI −6.02 to −3.10; I2 = 82.6%) and lower frequency of tonic–clonic seizures (WMD = −3.32; 95% CI −4.75 to −1.89; I2 = 96.4%). In addition, the distinct difference of adverse events was non-existent between two groups. Conclusions: Sodium valproate combined with TPM was more effective than sodium valproate alone for epilepsy therapy. This meta-analysis provides feasibility data for a larger-scale study on AED therapy of refractory epilepsy and may contribute to better therapy strategies for epilepsy clinically.